(untitled) (African Journal of Biomedical Research, 2019)
Snoring, a symptom of disordered breathing during sleep, is increasingly becoming a major public health concern. A significant correlation has been found between snoring and cardiovascular diseases; unfortunately, it remains under-diagnosed in general population. This study sought to determine the prevalence of snoring, knowledge and perception of health risks associated with it among postgraduate students of a tertiary institution in Southwestern Nigeria. Using multi stage sampling technique, 300 postgraduate students of the University of Ibadan were selected. A self-administered questionnaire, was used to collected data on their socio-demographic characteristics, knowledge and perception of snoring, its health risks and snoring patterns. A 21-point, 12-point, 15-point and 12-point scales was used to measure knowledge of snoring, knowledge of its health risks, perception related to snoring and perception of its health risks respectively. Scores ≥15, ≥9, ≥9 and >6 were cut-offs for good knowledge of snoring, knowledge of its health risks, perception related to snoring and perception of its health risks, respectively. Descriptive and inferential statistics were used to analyse the data at α0.05. Respondents age was 27.2±4.3 years and 53.3% were males. Knowledge of snoring was good among 53.3% of respondents, 13.3% had a good knowledge of health risks associated with snoring, 71% had good perception of snoring while 43% had good perception of health risks associated with snoring. Prevalence of snoring was 31.3% and was significantly higher among males (36.9%) than females (25.2%). The level of knowledge of health risks associated with snoring is inadequate indicating a need for increased awareness on health risks associated with snoring among adults in Nigeria.